(untitled) (African Multidisciplinary Journal of Research, 2024)
This article scrutinizes the motivations behind the Crusades initiated by Western European Christians, concentrating on religious, political, and cultural aspects. Analyzing the complex dynamics between Christians and Muslims during this period, marked by both conflict and cooperation. The study delves into various modes of communication, particularly cultural exchange, to foster a nuanced understanding of relationship dynamics. Emphasizing the lasting impact of the Crusades on Christian-Muslim relations, this article addresses the ongoing problem of the impact of the Crusades and their effects on the relationship between Muslims and Christians, whose echoes still resonate in contemporary perspectives. These effects remain engraved in the minds of many to the extent that some believe similar wars could recur today. The article aims to bridge the scholarly gap by examining the implications that influence the present relationship between Christians and Muslims, including in the African context. The article adopting a literature-based approach, relies exclusively on library sources for data collection, conducting a comprehensive review of scholarly works, books, and academic journals. This approach aims to gather insights from historical, and comparative perspectives, contributing to a thorough exploration and analysis of the subject matter.